Global economic divergence and portfolio capital flows to emerging markets - Zeyyad Mandalinci; Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2015)
This paper studies the role of global and regional variations in economic activity and policy in developed world in driving portfolio capital flows (PCF) to emerging markets (EMs) in a Factor Augmented Vector Autoregressive (FAVAR) framework. Results suggest that PCFs to EMs depend mainly on economic activity at the global level and monetary policy in America, positively on the former and negatively on the latter. In contrast, economic activity and policy shocks in Europe and Asia contribute significantly less to variations in PCFs to EMs. Hence, PCFs are driven by not only common shocks across all developed countries, but also variations in specific regions. This implies that economic divergence in the developed world can have significant effects on EMs via PCFs.
Keywords: C11; C32; E30; E52; E58; F32; 330; Portfolio capital flows; Bayesian analysis; Factor model; VAR; Emerging markets